(3CfhGQ GdabGgIs - (3GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ GdLfGMj, J (B1262(3g` (B1846(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdbQV HaJM GdbGa hcSQgG hgh dZI hTQYG Jedjc Yjf Ydi hLg jKHJ aj GdPeI eKdgG Ch bjeJgG Ch JedcgG dc Ch JedjcgG Ch JedcgG dc hHGdLedI aJYdbgG Ydi hLg eVs
(3BNQgG (B:s
(3BNQgG(B: (3aGdKGHJ ef GdGLeGY hGdVQhQI CjkVG YOe LhGR GdfbV dcf gd aj GdQhGjI OdGdI Ydi Pdc Ch QHeG jbGd HCf ajgG OdGdI fXQG Edi GdbVjI ajs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B1: 543s
(3GdPQjYI, L (B2: 244s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis